Diaphyseal fractures of the forearm in adults, comparative study of dynamic compression plate versus intramedullary nail - Venkataraman, Sagar; Ethiraj, Prabhu; Shanthappa Naik, Arun Heddur; Angadi, Sachin Prakash (International Journal of Research in Orthopaedics, 2019)
Background: Forearm fractures are common nowadays because of road traffic accident. It is important to achieve anatomical reduction of both bone forearm fractures to regain function of upper limb. This study is undertaken to observe functional and radiological outcome using two different surgical modalities like dynamic compression plating (DCP), and intramedullary nailing in both bone forearm fractures and also to indivualize the optimal treatment method for different fracture pattern. Methods: Our study included 60 patients with diaphyseal forearm fractures in adults presenting to orthopaedic outpatient department. Among 60 patients, 30 patients underwent open reduction and internal fixation by dynamic compression plate and other 30 patients underwent closed reduction/open reduction by square nail after detailed pre-operative evaluation. Results: In our study average union time in DCP group is 23.39 weeks and square nail group is 28.89 weeks. Union in DCP group was 27 (90%) and square nail group 22 (73.33%). Delayed union in DCP group was 03 (10%) and in Square nail group was 6 (20%), non-union in DCP group was 0 (nil) and in square nail group was 2 (06%). Conclusions: Open reduction and internal fixation with DCP plates for both bone diaphyseal forearm fractures gives good results with early union rates. We also found that in open fractures and complex fracture like segmental fractures square nailing was better option compared to dynamic compression plate to reduce infection rates, retain periosteal blood supply from soft tissue. Thus we conclude that both implants are equally important and we should prioritize based on preoperative planning.